2004
DOI: 10.1590/s0100-204x2004000800005
|View full text |Cite
|
Sign up to set email alerts
|

Atividade microbiana em solo do semi-árido sob cultivo de Atriplex nummularia

Abstract: Resumo -Métodos para avaliar a atividade microbiana no solo são fundamentais no monitoramento ambiental de áreas degradadas. O objetivo deste trabalho foi investigar a atividade microbiana de solo do semi-árido cultivado com Atriplex nummularia Lindl. em áreas que receberam rejeito salino durante um e três anos, em comparação com um solo nativo, sem cultivo e não irrigada. O solo cultivado por três anos e que recebeu rejeito salino apresentou, no período seco, valores de pH, CE e atividade de hidrólise do diac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
2
4
0
8
Order By: Relevance
“…The authors found that although the irrigation with saline waste affected the physical and chemical properties of the soil, cultivation of the halophyte favored microbial activity. Similar results were obtained by Pereira et al (2004) studying soil cultivated for three years with Atriplex nummularia Lindl., and irrigated with saline waste. In the dry periods, the values for pH, electrical conductivity, fluorescein diacetate hydrolytic activity and alkaline phosphatase activity were higher than in other areas.…”
Section: Plant Remediation Strategiessupporting
confidence: 85%
“…The authors found that although the irrigation with saline waste affected the physical and chemical properties of the soil, cultivation of the halophyte favored microbial activity. Similar results were obtained by Pereira et al (2004) studying soil cultivated for three years with Atriplex nummularia Lindl., and irrigated with saline waste. In the dry periods, the values for pH, electrical conductivity, fluorescein diacetate hydrolytic activity and alkaline phosphatase activity were higher than in other areas.…”
Section: Plant Remediation Strategiessupporting
confidence: 85%
“…The values for this variable (microbial biomass C) are within the range mentioned for savannas, gallery forest and eucalyptus forest (Behera and Sahani, 2003;Melloni et al, 2001); but lower values were observed in other native semiarid area in Northeast Brazil (Pereira et al, 2004). Probably the gypsum mining activity contribute for increasing the levels of pH in the studied areas (almost neutral), reducing the metabolic activity of the microbial community.…”
Section: Discussionsupporting
confidence: 68%
“…Confirming other studies, in some of the areas total soil enzyme was affected by the season, being higher during the wet than in the dry period. Conversely, greater enzyme activity (FDA) was found during the dry period in a semiarid soil cultivated with Atriplex nummularia (Pereira et al 2004). Swisher and Carroll (1980) demonstrated that this variable (hydrolysis of FDA) is directly proportional to the microbial population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Microbial respiration and the hydrolysis of fluorescein diacetate (FDA) are some of the parameters most commonly used to evaluate microbial activity in soils; they define the total enzymatic activity in a soil where microorganisms are the main source of enzymes (Pereira et al, 2004;Green et al, 2006;Batista et al, 2008;Carvalho et al, 2008;Carneiro et al, 2009;Evangelista et al, 2012). Research has shown that these factors are significantly influenced by soil use and management methods (Pell et al, 1998;Stenström et al, 1998;Arshad and Martin, 2002;Schloter et al, 2003;Gil-Sotres et al, 2005;Batista et al, 2008).…”
Section: Introductionmentioning
confidence: 99%